2010
DOI: 10.21608/eajbsf.2010.17465
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Effects of Some Heavy Metal Ions on Culex pipiens L. (Diptera: Culicidae)

Abstract: Different concentrations of selected heavy metals in the form of cadmium chloride (CdCl 2), copper sulphate (CuSO 4), lead nitrate (Pb (NO 3) 2) and mercuric nitrate (Hg (NO 3) 2) were tested against immature and mature stage of C. pipiens to assess the toxicity, LC 50 , total carbohydrate and lipid content. The survival potential of 2 nd instar larvae was highly affected by the contamination with the tested heavy metals. On the basis of LC 50 , Cd was the most toxic metal against the larval stage followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Another study showed that exposure to Cd treated soil produced destruction of mitochondria and microvilli border of cells in the digestive tract of Proisotoma minuta (Collembola) [35]. Some other corroboratory results on the ill effect of heavy metals on food uptake and assimilation, and tissue nutrient profile are in Isopoda Porcellio laevis [36], in Diptera Boettcherisca peregrine [37], and in mosquito Culex pipiens [38]. Most metals disrupt the enzyme functions by binding with sulphur groups in enzymes, and inhibition of enzymes may be due to the making of catalytically active groups or by protein denaturation [39].…”
Section: Effects Of Lead and Cadmium On Tissue Nutrients And Digestivmentioning
confidence: 87%
“…Another study showed that exposure to Cd treated soil produced destruction of mitochondria and microvilli border of cells in the digestive tract of Proisotoma minuta (Collembola) [35]. Some other corroboratory results on the ill effect of heavy metals on food uptake and assimilation, and tissue nutrient profile are in Isopoda Porcellio laevis [36], in Diptera Boettcherisca peregrine [37], and in mosquito Culex pipiens [38]. Most metals disrupt the enzyme functions by binding with sulphur groups in enzymes, and inhibition of enzymes may be due to the making of catalytically active groups or by protein denaturation [39].…”
Section: Effects Of Lead and Cadmium On Tissue Nutrients And Digestivmentioning
confidence: 87%
“…Invertebrates are good models to study toxicity of heavy metals and are useful bioindicators of contamination of the environment (Borowska and Pyza, 2011). Previous studies showed that toxicity of heavy metals on immune cells are related to the species, dose, the method of application, developmental stage of animals and animal's sensitivity (Kazimírová and Slovák, 1996;El-Sheikh et al, 2010;Suganya et al, 2016). Here, we tested the heavy metal toxicity at cellular levels and examined the lesser wax moth's hemocytes as an element of its immune system.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that Cd and Pb metals are toxic on S. litura larvae and cause strong oxidative stres. In another study El-Sheikh et al (2010) proved that the larval mortality percent of Culex pipiens L. (Diptera: Culicidae) larvae increased as the concentration of heavy metals namely; Cd, Cu, Pb and mercury (Hg) increased. In addition, Bischof (1995) reported that different types of metals significantly affects the biochemical composition of parasitized Lymantria dispar (Lepidoptera: Lymantriidae) larvae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El-Sheikh et al [82] studied the effect of different concentrations of selected heavy metals' salts against immature and mature stages of C. pipiens and they found that the potential survival of second instar larvae was highly affected by these salts. The number of eggs laid by females resulted from treated larvae decreased significantly and therefore, a lower fecundity was recorded for these females compared with control mosquitoes.…”
Section: Discussionmentioning
confidence: 99%